A record linkage study of antidepressant medication use and weight change in Australian adults. (November 2015) - Paige, Ellie; Korda, Rosemary; Kemp-Casey, Anna; Rodgers, Bryan; Dobbins, Timothy; Banks, Emily
Objective: Antidepressant use is widespread. While weight gain is a commonly reported side-effect of antidepressant use and has the potential to affect population health, there is little large-scale population-based evidence on the issue, particularly for long-term use (⩾12 months). The aim of this study is to investigate the association between antidepressant use and weight change, including whether this relationship varies according to antidepressant class, recency of use, duration of use and dose. Methods: Annual percentage weight change was calculated from self-reported weight at two time-points from 20, 751 participants aged ⩾45 years from the 45 and Up Study – a population-based cohort study from New South Wales, Australia. Antidepressant use, ascertained from linked pharmaceutical data, from 19 months before baseline until end of follow-up (mean = 3.3 years of follow-up), was categorised as current, past-only, non-persistent or non-use. The association between antidepressant use and weight change was modelled using linear and multinomial logistic regressions and according to antidepressant class, recency, duration and dose. Results: Antidepressants were dispensed to 23% of participants ( n = 4748) during the study period. Current antidepressant users were significantly more likely to gain >3% of their body weight annually than non-users (adjusted relative risk ratio = 1.19; 95% confidence interval: [1.03, 1.38]); the risk increased with increasing dose among current users ( p [trend] = 0.003). Risk of weight gain did not vary significantly according to antidepressant class, recency or duration of use; however, statistical power was limited. No significant associations were found between antidepressant use and weight loss. Conclusion: Current antidepressant use was associated with modest but statistically significant annual gains in weight, with similar effects observed across the different classes of antidepressants used.